Awake prone positioning for patients with COVID-19 pneumonia in intensive care unit: A systematic review and meta-analysis - Huang, Hui-Bin; Yao, Yan; Zhu, Yi-Bing; Du, Bin (Frontiers in Medicine, 2022)
Background Awake prone positioning (APP) has been widely used in non-intubated COVID-19 patients during the pandemic. However, high-quality evidence to support its use in severe COVID-19 patients in an intensive care unit (ICU) is inadequate. Therefore, we aimed to assess the efficacy and safety of APP for intubation requirements and other important outcomes in this patient population. Methods We searched for potentially relevant articles in PubMed, Embase, and the Cochrane database from inception to May 25, 2022. Studies focusing on COVID-19 adults in ICU who received APP compared to controls were included. The primary outcome was the intubation requirement. Secondary outcomes were mortality, ICU stay, and adverse events. Study quality was independently assessed, and we also conducted subgroup analysis, sensitivity analysis, and publication bias to explore the potential influence factors. Results Ten randomized controlled trials with 1,686 patients were eligible. The quality of the included studies was low to moderate. Overall, the intubation rate was 35.2% in the included patients. The mean daily APP duration ranged from <6 to 9 h, with poor adherence to APP protocols. When pooling, APP significantly reduced intubation requirement (risk ratio [RR] 0.84; 95%CI, 0.74–0.95; I2 = 0%, P = 0.007). Subgroup analyses confirmed the reduced intubation rates in patients who were older (≥60 years), obese, came from a high mortality risk population (>20%), received HFNC/NIV, had lower SpO2/FiO2 (<150 mmHg), or undergone longer duration of APP (≥8 h). However, APP showed no beneficial effect on mortality (RR 0.92 [95% CI 0.77–1.10; I2 = 0%, P = 0.37] and length of ICU stay (mean difference = −0.58 days; 95% CI, −2.49 to 1.32; I2 = 63%; P = 0.55). Conclusion APP significantly reduced intubation requirements in ICU patients with COVID-19 pneumonia without affecting the outcomes of mortality and ICU stay. Further studies with better APP protocol adherence will be needed to define the subgroup of patients most likely to benefit from this strategy.